APLIKASI PENGELOLAAN DATA ALUMNI BERBASIS WEB PADA STMIK AKAKOM MENGGUNAKAN METODE WATERFALL - Indra Yatini Buryadi; Sur Yanti (LPPM STMIK El Rahma Yogyakarta, 2020)
The Alumni and Akakom Career Center (ACC) of STMIK Akakom is tasked with managing alumni and career data of the alumni. The implementation of ACC activities in the tracer study was carried out on a computerized basis using google forms which would then be downloaded in the form of excell to produce reports. The purpose of this research is to develop a web-based STMIK AKAKOM alumni data management application with the waterfall method that can be used by the Alumni Section and Akakom Career Center to manage tracer study data. The scope of the research includes the management of alumni data collection as a means of evaluation and reporting to the leadership or as an accreditation instrument of PT. Data collection techniques include observation, documentation and interviews. There are 3 (three) entities involved in this system, namely the ACC, Management and Alumni Sections, each of whom has access rights to log into the system. Data processed in the system includes survey name data, alumni data, alumni survey question data and alumni answer data. The application system for tracer study generated is web-based with the waterfall method.